Daily variations in Western Greenland slush limits, 2000–2021 - Horst Machguth; Andrew J. Tedstone; Enrico Mattea (Journal of Glaciology, 2023)
The marginal areas of the Greenland ice sheet develop streams and lakes each summer, documenting that surface runoff of meltwater is a major component of ice-sheet mass balance. Here we map the slush limit, a proxy for the extent of surface runoff, using daily MODIS data for the years 2000–2021. We develop an automated algorithm capable of detecting daily slush limits, provided sufficient image quality. The algorithm is applied to the ice sheet's western flank (61.7 $^{° }$N to 76.5 $^{° }$N). We find significant increasing trends in maximum slush limits until the year 2012, but not thereafter. We show that the slush limit typically rises quickly early in the ablation season but stabilizes before melting ceases. The data provide evidence that upward migration of surface runoff in summer 2012 stopped early at the upper margin of the ice slabs. These thick and continuous ice layers are located close to the surface, in the firn, and impede percolation of melt into deeper pore space. Had the ice slabs extended higher, the summer 2012 provided sufficient energy to raise the slush limit by another $\sim$300 m in elevation.